Based on the Principle, Application, and Future Development Direction of Synthetic Aperture Radar Technology - Li, Haoyi (Transactions on Computer Science and Intelligent Systems Research, 2024)
Synthetic Aperture Radar (SAR) originated from military needs during the Second World War. Today, this technology has become an important tool for Earth observation in many fields, including environmental monitoring, military reconnaissance, resource exploration, disaster monitoring, agricultural applications, marine research, and urban management. This article will elaborate on the basic principles of SAR, including its range and azimuth resolution, as well as the relevant techniques for carrier flight. At the same time, the progress of SAR technology in multiple research directions will be discussed, especially its application in earthquake disaster monitoring and rescue, geological exploration and resource exploration, agricultural monitoring and crop growth assessment, marine monitoring and environmental protection, urban planning, and land use, etc. Finally, the paper will also look forward to the future development of SAR technology and highlight its potential to advance geoscience research and practical applications.